Disciplinary standards of IL education - Jauhiainen, Ilmari; Hintikka, Kristiina (Qualitative and Quantitative Methods in Libraries, 2019)
This paper attempts to show that LibQUAL+ tool can be used to measure how the perceptions of and standards required for library instruction differ across disciplines in the different university libraries from different countries. The paper suggests, firstly, that the quality of library IL instruction does not directly correlate with the resources put into the instruction, secondly, that a high-quality IL instruction raises demands for more IL instruction, and thirdly, that good IL instruction leads to consistent standards of IL education in different disciplines. Furthermore, interesting disciplinary differences in the satisfaction of and demands to IL education are revealed.